Illustrated and online catalog of the type specimens of birds (Class: Aves) in the Ornithological Collection at the Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-A), Colombia - Córdoba-Córdoba, Sergio; Sierra, Socorro; Borja-Acosta, Kevin Giancarlo (Zootaxa, 2018)
The catalog of type specimens of birds deposited in the Bird Collection of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-A) is presented. The list includes 10 specimens representing two holotypes and eight paratypes of three nominal species and five nominal subspecies. Three specimens also have tissues deposited in the Tissue Collection of the Instituto Humboldt (IAvH-CT). Corrections, additions, and updated information of the original descriptions and geographic locations are included as individual remarks for each catalog number and a gallery of photographs of each specimen is provided. An online version of the catalog is available at: http://colecciones.humboldt.org.co/catalogos/tiposaves